Dermoscopy to detect signs of subclinical nail involvement in chronic plaque psoriasis: A study of 68 patients - Tulika A Yadav; Uday S Khopkar (Wolters Kluwer Medknow Publications, 2015)
Background: Onychopathies constitute one of the major challenges faced by a dermatologist in terms of its early detection and diagnosis. Utility of dermoscope as a tool for detection is increasing by the day and its use in onychopathies needs to be explored. Aims: To study the dermoscopic features of nails in patients of chronic plaque psoriasis. Materials and Methods: In a cross-sectional study, a total of 68 patients with chronic plaque psoriasis were recruited. Dermoscopy of nail plate was conducted and were compared with equal number of age and sex matched healthy volunteers. Results: Forty-six patients showed dermoscopic findings. Twenty-two patients did not show any dermoscopic findings. Coarse pits (18/46, P < 0.0001), onycholysis (10/46, P < 0.001), oil drop sign (2/46, P = 0.12) and splinter hemorrhages (5/46, P = 0.05) were seen. In addition certain findings of interest were stout, globose, dilated, pink- to red-colored nail bed vessels arranged longitudinally at the onychodermal band surrounded by a prominent halo (9/46, P = 0.01). In contrast, splinter hemorrhages appeared as streaks and were purple in color. Conclusion: In a psoriasis patient, dermoscope can be a useful tool to detect early nail involvement in psoriasis and aid in differentiating it from other disorders of nails.